Effect of banana (Musa spp.) intercropping with root and tuber crops (Current Horticulture, 2024)
A field experiment was conducted at the Odisha University of Agriculture and Technology (OUAT), Bhubaneswar, Odisha to evaluate the performance of intercropping of banana cv. Champa with elephant-foot yam, ginger, turmeric, arrow root, colocasia and mango ginger during 2011-16. Growth and yield characters of banana did not show any significant difference among each other, indicating that cultivation of intercrops does not have any significant effect on them. Yield of intercrops varied from 13.29 tonnes/ha in elephant-foot yam to as high as 54.84 tonnes/ha in mango ginger. However, arrow root recorded maximum returns of ` 3.54 lakh/ha. Banana + arrow root combination recorded maximum total returns (` 8.21 lakh/ha), net profit (` 5.29 lakh/ha) as well B:C ratio (2.09). The effect of intercropping on incidence of Eumusae leaf spot showed that except colocasia, other intercrop combinations had significantly higher PDI than growing banana alone (PDI 8.75). The maximum PDI was recorded in banana + turmeric (27.50), followed by banana + mango ginger (26.25). Banana + arrow root recorded a moderate leaf spot incidence of 17.50 necessitating the application of suitable systemic/contact fungicide while growing arrow root as an intercrop in banana. Two pathogenic nematode species, viz., reniform nematode, (Rotylenchulus reniformis) and root-knot nematode, (Meloidogyne incognita) were recorded. In none of the treatments, these two pathogenic nematodes were above the economic threshold level (ETL). The population of Rotylenchulus reniformis in banana + arrow root was 104 per 250 g soil, against ETL of 1000 young females per 250 g soil. Thus it is concluded that arrowroot can be taken as a remunerative intercrop in banana in Odisha..
Keywords: Intercrop; Benefit : cost ratio; Arrow root; Nematode; Eumusae; Root and tuber crops